(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article demonstrates that new requirements and challenges open new perspectives in forming the habitat and architectural creativity due to technical and technological capabilities. The architects` role and place in the integration processes of a technocratic society are analyzed. The main reasons for the loss of leading positions in the construction industry by modern architects are determined. The unique role of the "syntheticity" of contemporary architecture is singled out. It is shown that modern architecture is turning from a monocultural phenomenon into a symbiosis of creative, cultural, scientific, and technical potentials. The example of the buildings "Vertical Forest" (Bosco Verticale) in Milan or the "Tower of Cedars" (La tour des Cedres) in Lausanne, the complex of the concert hall "Maraya" in the Al-Ula desert of Saudi Arabia, the convention center in Changzhou Park in China, the active participation of design engineers in the creative process of design and construction, the introduction of "green" technologies and materials, the implementation of the principles of the following "sustainable" construction is shown. The study emphasizes that the design of complex engineering systems and mechanisms significantly complicates the process of architectural and building design. It requires the architect to go beyond the scope of the profession fundamentally. It is pointed out that the alienation of a person from architecture has become an obvious deep problem of architectural activity at the level of the author-architect, the consumer-addressee, and at the level of development, transformation, and implementation of the project. Several reasons have been identified that do not allow most architects to become the head of a complex mechanism for implementing their creative intent. It is proved that the full development of the architect in the working process is possible only in large architectural firms. The importance of a dynamic process of improving modern management technologies in large architectural firms, and more active public involvement at all stages of construction and investment activities, is emphasized. It is argued that small architectural bureaus cannot guarantee their employees the development of quality of their professional horizons. One of the ways to solve these problems is proposed. It is argued that the capabilities of modern digital technologies, scientific and technical discoveries, and the inconsistency of the integration process, bring many new and specific trends to architectural activity. The tendency of gradual improvement of constructive-plastic, functionaltechnical, and artistic-aesthetic qualities in mass construction is revealed.